Productivity improvement in honing machining process. (2022) - Mawandiya, Bimal Kumar; Sonagara, Akshay; Balar, Tejas; Patel, Kaushik M.; Shah, Dhaval B.
Abstract: In the past few years, legislation regarding fuel consumption and its emission levels for the automotive industry has become increasingly comprehensive. The friction generated in the engine should be minimum to reach the demands for automotive manufacturers. The cylinder liner is considered to be one of the most critical engine components regarding friction and different surface texture. Honing is one of the best machining processes to create efficient cylinder liners. In this research paper, the key parameters have been identified in the process control connected to surface roughness by optimizing the honing process in cylinder liner manufacturing in the automobile industry. Furthermore, the aim is to find an optimal setting of the machine to produce the demanded surface texture. After viewing the results of the test, it has been noticed that plateau honing plays an important role in the surface texture quality. The factors which affected the honing process were namely honing force, stroke length, reciprocating speed, expansion point and rpm. Out of all these, for a given situation, the required important parameter is identified to achieve stipulated cycle time and required surface quality.